1982
DOI: 10.1111/j.1748-5827.1982.tb02519.x
|View full text |Cite
|
Sign up to set email alerts
|

Water balance in the dog and cat

Abstract: In respect of its metabolic control of water balance, the cat probably differs as much from the dog as it does in most other respects. In qualitative terms the routes of gain and loss of water are very much the same: in quantitative terms and in its homeostatic response to different environmental stimuli or insults the cat and the dog are rather different. Dogs and cats are among the commonest species with which veterinarians have to deal. They share much the same environment and are treated in much the same w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The diet fed to the cats in the present study contained 82% moisture and after 2 days of food restriction, urine volume decreased rapidly to approximately 10 ml/kg body weight. This is in line with other observations showing that cats fed moist cat foods have a higher urinary output compared to cats fed semimoist and dry diets (ANDERSON 1982;GASKELL 1989). WAMBERG et al (1996b) also observed a marked drop in urine output of farmed mink fed a moist diet when food was withheld.…”
Section: Study 1: Accuracy Of Urine Collection In Adult Catssupporting
confidence: 93%
See 1 more Smart Citation
“…The diet fed to the cats in the present study contained 82% moisture and after 2 days of food restriction, urine volume decreased rapidly to approximately 10 ml/kg body weight. This is in line with other observations showing that cats fed moist cat foods have a higher urinary output compared to cats fed semimoist and dry diets (ANDERSON 1982;GASKELL 1989). WAMBERG et al (1996b) also observed a marked drop in urine output of farmed mink fed a moist diet when food was withheld.…”
Section: Study 1: Accuracy Of Urine Collection In Adult Catssupporting
confidence: 93%
“…Accurate measurement of water balance in animals is often difficult as many in-and output values have to be determined (ANDERSON 1982) such as food water intake, drinking water intake, urinary water excretion, faecal water excretion, water lost through expired air, etc. Furthermore, an estimate of metabolic water production is required as well as estimates of evaporative losses of water from urine, food, drinking water, etc.…”
Section: Study 2: Accuracy Of the Conventional Water Balance Techniqumentioning
confidence: 99%
“…25 In the same study, increasing the salt content of the diet caused an increased drinking response in both dogs and cats. For example, in a study of dogs that were fed a diet containing 73% moisture, they obtained 38% of their daily water needs from drinking water.…”
Section: Box 1-1 Samplecalculationto Estimateamountoffood Requireddailymentioning
confidence: 87%
“…Obesity is the commonest nutritional disease of companion animals. In various countries the prevalence has been reported as being from 19% to 52% in domestic cats (31)(32)(33)(34) and from 22 % to 44 % in dogs (31,(35)(36)(37) . Orthopedic, endocrine, cardiac, respiratory, neoplastic, urinary, reproductive and dermatological disease and reduced resistance to infection have been associated with obesity in dogs and cats (38) .…”
Section: Prevention Of Diseasementioning
confidence: 99%